RISK MANAGEMENT TO MAXIMIZE BUDGET LIMITATION: CASE STUDY VEENATURALS - Triyanto, Nurfatin
In this digital era, social media is no longer just a means of entertainment, but has become a part of everyday life that is as important as eating and resting, even for some people, social media is like their life. The high intensity of using social media not only provides convenience and entertainment, but also raises several social problems, such as standardization of beauty, feelings of lack of confidence, and so on. Therefore, the use of makeup emerged as a way to increase one's self-confidence. However, the use of makeup that is not careful can have harmful long-term effects. Some of the causes include the use of hazardous materials. Therefore, Veenaturals as a solution by producing cosmetic products that use natural ingredients. As a business in beauty industry, Veenaturals must quickly adapt to be much better than its competitors. However, business is not possible without obstacles. In doing so, Veenaturals will face many risks that will interfere, both internally and externally. This can happen because the dynamics of the business in the beauty sector are running very fast. Good risk management can help Veenaturals to prepare a strategy carefully. The methodology used is through interviews with internal stakeholders to identify internal risks. Internal parties involved include all departments at Veenaturals, including operations, finance, marketing, and human resources. Then from the external side of life, the parties involved are Veenaturals or similar beauty products. Based on the results of the risk analysis identified from this study, there are 43 internal risks and 31 external risks. Based on this risk analysis, Veenaturals will assess risk mitigation strategies and plans for the future benefit of the company.